In vitro and in vivo antitumor effects of chloroquine on oral squamous cell carcinoma - Jia, Lihua (Mol Med Rep, 2017)
Chloroquine, which is a widely used antimalarial drug, has been reported to exert anticancer activity in some tumor types; however, its potential effects on oral squamous cell carcinoma (OSCC) remain unclear. The present study aimed to explore the effects and possible underlying mechanisms of chloroquine against OSCC. MTT and clonogenic assays were conducted to evaluate the effects of chloroquine on the human OSCC cell lines SCC25 and CAL27. Cell cycle progression and apoptosis were detected using flow cytometry. Autophagy was monitored using microtubule-associated protein 1A/1B-light chain 3 as an autophagosomal marker. In order to determine the in vivo antitumor effects of chloroquine on OSCC, a CAL27 xenograft model was used. The results demonstrated that chloroquine markedly inhibited the proliferation and the colony-forming ability of both OSCC cell lines in a dose- and time-dependent manner in vitro. Chloroquine also disrupted the cell cycle, resulting in the cell cycle arrest of CAL27 and SCC25 cells at G(0)/G(1) phase, via downregulation of cyclin D1. In addition, chloroquine inhibited autophagy, and induced autophagosome and autolysosome accumulation in the cytoplasm, thus interfering with degradation; however, OSCC apoptosis was barely affected by chloroquine. The results of the in vivo study demonstrated that chloroquine effectively inhibited OSCC tumor growth in the CAL27 xenograft model. In conclusion, the present study reported the in vitro and in vivo antitumor effects of chloroquine on OSCC, and the results indicated that chloroquine may be considered a potent therapeutic agent against human OSCC.